Reflections of an Ontario Student Teacher in Scotland: Cultural Language and Cross-Cultural Classroom Management - Alexandra Gayowsky (University of Windsor, 2019)
A new teacher in her initial teacher education (ITE) program is focused on curriculum content, classroom management and pedagogy, and this perspective does not change despite a variation in the cultural context (Hassaram, Robertson, & Garcia, 2019). "Reflections of an Ontario Student Teacher in Scotland" is a narrative of raw, qualitative reflexive data composed during a one-week period of ITE practice teaching placement in Northern Scotland (Clarà, Mauri, Colomina, & Onrubia, 2019). The English teacher-narrator identifies the language differences, comparative abilities in writing, and those one-on-one connections between student teacher and pupils that allow for a rewarding reciprocal learning experience in first year classroom management and teaching.